The Azores Confluence Zone - Caldeira, Rui M. A.; Reis, Jesus C. (Frontiers in Marine Science, 2017)
The goal of this study is to characterize the meteorological and oceanographic conditions affecting the Azores Archipelago, and explore their biological implications. The Mid-Atlantic region of the Azores Archipelago is under the permanent influence of the Azores high pressure system, thereby providing sustained Ekman transport that facilitates the convergence in regional oceanography. The west and central island groups are affected by incoming meanders and filaments originating in the Gulf Stream, whereas the east island group is most affected by westward propagating eddies pinching-off from the Azores Current. Output from the European Centre for Medium-Range Weather Forecasts are combined with altimetry data to study the dynamic oceanographic processes affecting the archipelago. Satellite-derived sea surface temperature and sea surface chlorophyll data are used as proxies to examine the biological enrichment processes. Climatological data analysis permits differentiation of the oceanographic systems that reach the west versus those that affect the east island groups. This is the first study to document the Azores as an oceanic confluence zone and demonstrate the associated biological impacts.